Sistem Pembelajaran Kitab Kuning sebagai Langkah Strategis dalam Menunjang Profesionalitas Guru Agama dalam Meningkatkan Wawasan Agama Peserta Didik - Lalu Abdurrahman Wahid; Eva Latipah; Habibuddin Ritonga (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Modernization of Islamic education has a significant impact on the interest of students in deepening religious insight. Students are more interested in general nuanced sciences such as English and other exact sciences. So it is necessary to take strategic steps in supporting the increase in motivation and religious insight of students. This study aims to build an argument about the existence and effectiveness of learning the yellow book in order to increase the religious insight of the students as students. This research includes field research with a phenomenological approach. Data collection was carried out by direct interviews with leaders and caregivers and several students as respondents. The results of the study explain that the implementation of learning the yellow book at the Madinatul Ulum Islamic boarding school, NW Mumbang is considered conducive and classified as maintaining resistance to Islamic education which aims to develop religious insight through learning the yellow book. The yellow book learning activities in Islamic boarding schools are considered quite effective and representative in increasing and developing students' religious knowledge. Through this yellow book learning activity, it is considered quite representative in supporting the professionalism of religious teachers in increasing the religious knowledge of students.